Moral Values in Five Novels by Syahid Muhammad - Agus Nuryatin; Deby Luriawati Naryatmojo; Ahmad Nur Cahyo (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
Novels contain moral values so that the author is able to convey meaning to readers through stories that describe the author's thoughts and thoughts about the value of truth related to a person's morals or manners. Moral values are important values because they form the basis for behavior. Instilling moral values can be done in the world of education through studying literature. Literature learning can provide students with an understanding of moral values. This research aims to explain the moral values in five novels by Syahid Muhammad. The approach used is a pragmatic and structural approach as well as descriptive analysis. Research data was obtained through semiotic reading, namely heuristic reading. Data were analyzed using hermeneutics. This research obtained the results that the five novels by Syahid Muhammad contained three moral values, namely the moral value of human relationships with God, the moral values of human relationships with themselves, and the moral values of human relationships with other humans. Moral values that have a relationship between humans and God include prayer, gratitude, faith, piety, trust, and regret. Moral values that have a relationship between humans and themselves include honesty, responsibility, healthy living, discipline, hard work, self-confidence, entrepreneurial spirit, logical thinking, creative innovation, independence, curiosity and love of knowledge. Finally, there are moral values that relate to the relationship between humans and other humans, including caring for others, helping each other, deliberation, living in harmony, forgiveness, keeping promises, and respecting other people. The more dominant moral values are prayer, gratitude, honesty, logical thinking, creativity, innovation, caring for others, forgiveness, respect for others